The SME Banking Knowledge Guide - International Finance Corporation (Washington, DC, 2016)
Can small and medium enterprises (SME) be banked profitably, and is the market today an attractive one? How do banks overcome the challenges and capture the opportunities offered by the SME segment, particularly in developing countries? What is the difference between SME lending and SME banking? How can banks successfully expand their SME banking operations? These are the types of questions explored in the SME Banking Knowledge Guide. This Guide provides an overview of the current state of SME banking, and then breaks down the approaches that banks are using to unlock the potential opportunity in a challenging, but growing market. It concludes with guidance for banks that want to begin to strategically engage the SME market.